Giant Ewing’s Sarcoma of the Body of the Scapula - Agrawal, Alok Chandra (J Orthop Case Rep, 2020)
INTRODUCTION: Ewing sarcoma is a malignant neoplasm occurring usually in bones such as femur, tibia, and iliac wing. We are here reporting a case of same arising from scapula. Of all the tumors arising from scapula, Ewing’s sarcoma contributed to only 8%. CASE REPORT: A male patient presented to us with pain and swelling over right scapular region. After initial investigation, biopsy was performed. Biopsy reveals uniform small-sized cells arranged in layers with high nucleus to cytoplasmic ratio. Provisional diagnosis of Ewing sarcoma was made which was later confirmed on immunohistochemistry. The patient underwent planned surgery after neoadjuvant chemotherapy, and swelling along with partial scapula was resected. CONCLUSION: Although Ewing sarcoma is common neoplasm, it rarely arises from flat bone-like scapula. Henceforth, reporting of such a case is not only imperative but also mandatory.